Determination of Nitrite and Nitrate in Water Samples by an Automated Hydrodynamic Sequential Injection Method - Somnam S. (2014)
An automated hydrodynamic sequential injection (HSI) system with spectrophotometric detection was developed. Thanks to the hydrodynamic injection principle, simple devices can be used for introducing reproducible microliter volumes of both sample and reagent into the flow channel to form stacked zones in a similar fashion to those in a sequential injection system. The zones were then pushed to the detector and a peak profile was recorded. The determination of nitrite and nitrate in water samples by employing the Griess reaction was chosen as a model. Calibration graphs with linearity in the range of 0.7 - 40 μM were obtained for both nitrite and nitrate. Detection limits were found to be 0.3 μM NO2- and 0.4 μM NO3-, respectively, with a sample throughput of 20 h-1 for consecutive determination of both the species. The developed system was successfully applied to the analysis of water samples, employing simple and cost-effective instrumentation and offering higher degrees of automation and low chemical consumption. © 2008 The Japan Society for Analytical Science